2016
DOI: 10.1097/qad.0000000000001219
|View full text |Cite
|
Sign up to set email alerts
|

Statin drugs decrease progression to cirrhosis in HIV/hepatitis C virus coinfected individuals

Abstract: Introduction Chronic HIV/HCV co-infection carries increased risk of cirrhosis, hepatocellular carcinoma, and death. Due to anti-inflammatory properties, HMG co-A inhibitors (statins) may be useful adjunctive therapy to reduce liver disease progression. Methods Clinical information was extracted from the Veterans Affairs HIV and HCV Clinical Case Registries (1999–2010). HIV-related variables included combination anti-retroviral therapy (cART) era of diagnosis, CD4 cell count, and percent time with undetectabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 41 publications
0
21
1
1
Order By: Relevance
“…Of the 1706 unique studies identified using our search criteria, 13 studies met our inclusion criteria and were included in our meta-analysis (3 RCTs and 10 observational studies) 3343, 50, 51 Six studies included participants with non-cirrhotic CLDs 35, 3943 , six studies included participants with compensated cirrhosis 36, 37, 42, 43, 50, 51 , and three studies included individuals with decompensated cirrhosis 33, 34, 38 . One study was excluded as it represented a population already included in another, more recent study; 52 one small RCT of statins in NASH was excluded due to insufficient information 53 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 1706 unique studies identified using our search criteria, 13 studies met our inclusion criteria and were included in our meta-analysis (3 RCTs and 10 observational studies) 3343, 50, 51 Six studies included participants with non-cirrhotic CLDs 35, 3943 , six studies included participants with compensated cirrhosis 36, 37, 42, 43, 50, 51 , and three studies included individuals with decompensated cirrhosis 33, 34, 38 . One study was excluded as it represented a population already included in another, more recent study; 52 one small RCT of statins in NASH was excluded due to insufficient information 53 .…”
Section: Resultsmentioning
confidence: 99%
“…Five studies reported risk of development of cirrhosis (or progression of fibrosis) in patients with baseline non-cirrhotic CLDs 35, 3941, 43 . In three studies, diagnosis of cirrhosis (or fibrosis progression) was ascertained based on a combination of administrative claims codes and calculated serum fibrosis markers (FIB-4 or APRI); one study was a post-hoc analysis of the HALT-C trial included patients with paired liver biopsies, with fibrosis progression defined based on increase in Ishak fibrosis stage by ≥ 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to medications and fibrosis progression, a retrospective study of 5,985 HIV/HCV co-infected veterans suggested statin use may be associated with slower fibrosis progression, although this finding was only significant in a sub-cohort of patients with low ALT [67]. An exploratory study in co-infected patients with concomitant non-alcoholic steatohepatitis showed 48 weeks of pioglitazone therapy resulted in reduced hepatic fat measured by magnetic resonance spectroscopy [68].…”
Section: Non-viral Causes Of Fibrosis Progressionmentioning
confidence: 99%